Meningkatkan Kemampuan Berhitung Permulaan Melalui Metode Math Training for Kid’s Application - Ibrahim, Khemal; Syamsul, Andi Nur; Uminar, Ajeng Ninda (Saneskara: Journal of Social Studies, 2024)
The problem of students' numeracy skills has long been a problem. The problem is low numeracy skills and uninteresting learning; students' initial numeracy skills do not develop. Although not all students, based on the teacher's notes, this was quite disturbing because of the 18 students, 8 still got scores that were far below the KKM with an average score of 50.6, while the KKN required 65 for the minimum complete score that students had to get in mathematics learning for all the subjects studied. This research targets 18 students by implementing the Math Training for Kids application as a solution to the Beginning Numeracy problem, which is implemented using a PTK model with 2 cycles. The results of the research show that students' initial numeracy skills (subtraction and addition) can be improved through practicing word problems with the help of the math training for kids application for class I students at SDN 429 Sagenae. In terms of tests, students' numeracy skills or activities are all above the KKM number determined in class I at SDN 429 Sagenae. We can compare them. On average, it was 76.66 (cycle I) and changed to 87.22 (cycle II), which means it has been classically completed. When referring to classical completeness (%) then the action has fulfilled 80%.